Biodiversity and Ecosystem Functions Across an Afro-Tropical Forest Biodiversity Hotspot - Seifert, Tobias; Teucher, Mike; Ulrich, Werner; Mwania, Felistas; Gona, Francis; Habel, Jan Christian (Frontiers in Ecology and Evolution, 2022)
Ecosystem functions are important for the resilience of ecosystems and for human livelihood quality. Intact habitats and heterogeneous environments are known to provide a large variety of ecosystem functions. Natural and near natural ecosystems surrounding agroecosystems may positively support crop growing conditions and thus facilitate crop yields. In contrast, monocultures of crops and trees as well as degraded landscapes are known to provide less ecosystem functions. The Taita Hills in southern Kenya are part of the Eastern Afromontane biodiversity hotspot, and represent a habitat mosaic consisting of largely intact cloud forests, agroecosystems and plantations of exotic trees. In this region, subsistence farmers rely on ecosystem functions provided by natural ecosystems. In this study, we analyse three proxies of biodiversity and ecosystem functions, namely pollination activity, predation rates, and arthropod diversity in tree canopies. We set study plots along forest-agroecosystem-gradients, covering cloud forest, forest edge and agricultural fields, as well as plantations of exotic trees. We assessed environmental conditions, to evaluate the extent to which local environmental factors influence ecosystem functions. Based on these data we investigate potential spill over of ecosystem functions from forest into adjoining agroecosystems. For predation rates we found trends of spill over effects from forest interior into the agroecosystem. The expression of ecosystem functions differed among habitat types, with comparatively high predation rates in the forest, high pollinator activity in the open agricultural areas, and highest arthropod diversity along the forest edge. Eucalyptus plantations showed reduced ecosystem functions and lowest arthropod diversity. Local factors such as vegetation cover and flower supply positively influence pollinator activity. Our study show that natural ecosystems may positively contribute ecosystem functions such as predation, while the homogenization of biota through planting of invasive exotic tree species significantly reduce biodiversity and ecosystem functions. Transition habitats such as forest margins, and small-scale ecological enhancement positively influences biodiversity and ecosystem functions.